ANALISIS TATA LETAK RITEL TOKO KELONTONG MELALUI METODE ACTIVITY RELATIONSHIP CHART (ARC) DAN TOTAL CLOSENESS RATING (TCR) - Ahmad Rizky Despati; Arizky; Fikri Asshidiqi; Muhamad Abian Razaki; Muhammad Al Fatih (Jurnal Riset Multidisiplin Edukasi, 2025)
Retail layout plays a strategic role in determining operational efficiency and customer convenience. This study aims to analyze and redesign the product display layout at CS Wholesale and Retail Store in Sukabumi Regency using the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. Data collection was conducted through direct observation and interviews with store personnel. The data obtained was then analyzed descriptively by identifying the proximity relationship between product categories and converting it into numerical values to determine shelf placement priorities. The results showed that the initial layout was not yet optimal due to the unsystematic arrangement of products and the absence of clear zoning, making it difficult for consumers to find items and hindering movement flow within the store. Based on TCR calculations, the beverage category had the highest correlation value and became the top priority in the rearrangement, followed by the snack and staple food categories. The redesigned layout resulted in more structured product zoning, clarified the consumer shopping flow, and improved space utilization efficiency and customer comfort. Thus, the application of the ARC and TCR methods proved to be effective as a systematic approach to optimizing retail layout and improving grocery store service quality.